ANALISA UMUR EKONOMIS UNTUK MENENTUKAN WAKTU PEREMAJAAN YANG OPTIMAL BAGI MESIN MOULDING - Giatman, Muhammad (Sainstek, 2009)
PT. Andalas Lumber Products is a company engaged in manufacturing semi-finished wood (sawn timber). The company's success in serving customer demand on time is determined by the readiness of the facility in carrying out its functions. One of the main engine is a molding machine is the machine used for the finishing process. The ability of these hourly Moulding machine is 600 m / hr working hours per day 7 hours, so if the machine does not operate in a single day because of damage to the business may experience a loss of 4200 m / hour. This machine consists of three units of the machine, which was 9 years old, in theory the economic life of 10 years for type machine Unimat 23E and 22N Profimat 8 years. This category of critical engine unit, therefore it is necessary that good maintenance schedule and a schedule of renovation that is right for the machine. In this research study and analysis of economic life cycle through the calculation of the estimated operating expenses, depreciation calculations, and determination of the cost of return on capital (capital recovery cost) by using an interest rate of 10%. Replacement schedule will be taken through the smallest total cost is considered as the economic life of the machine where the costs incurred is minimum. From the results obtained by processing data from the smallest total cost of Rp molding machines I 157,240,725.3 with economic life in its 7th year, molding machine II of Rp 112 551 903 with the economic life of Rp 156,391,605.3 the economic life of the year-to-7. With both types of machines are economical replacement should have been done. Key words : Economic life-cycle, Capital-Recovery, Replacement